(untitled) (Med Phoenix, 2021)
Introduction: Sonographic evaluation of the carotid artery is commonly used for risk assessment in stroke. In Nepal, there are few studies regarding morphological changes in the carotid artery including the percentage of stenosis, types of plaque, sites of plaque. These changes quite vary in relation to age, sex, and ethnicity, and other risk factors. The primary objective of the study was to find the prevalence of carotid plaques in different ethnic groups with ischemic stroke. Materials and Methods: The study was an observational, cross-sectional descriptive study conducted in the Neuromedicine department of the National Academy of Medical Sciences. The study included a consecutive sampling of the patients diagnosed with ischemic stroke admitted in the neuro/medicine ward or those visiting neuro/medicine OPD of Bir hospital. Results: Out of the 80 study patients,26.3% patients were Brahmans/Chhetri,11.3% were Madhesi,10 % were Dalits,25% were Newars and 27.5% were Janajati. In descending order, the presence of carotid plaque in Janajati (20%) was followed by Newars (18.8), Brahmans (17.5%), Madhesi group (8.8%), and Dalit (7.5%). The mean number of plaque was higher in Brahman/Chhetri group 3.33 with S.D 3.28 and lowest in Janajati group 2.20 with S.D 3.16. It was found that around 24% of the cases had unilateral carotid plaques and 49% had bilateral carotid plaques. Janajati group had a maximum proportion of bilateral plaques while Dalit had the least proportion (15% vs 2.5%). However, the difference among the ethnic groups was not significant. Conclusion: The prevalence of carotid plaques, the maximum number of plaques, and the number of bilateral plaques, all were highest in the Janajati group. However, the mean number of the carotid plaque was highest among the Dalit group. Further larger studies are required to study the association of the Nepalese ethnicity with carotid morphological changes.